Assessment of Neutrophil- Lymphocyte and Platelet- Lymphocyte Ratios in Ankylosing Spondylitis - İsmail BOYRAZ and Bünyamin KOÇ and Sirzat ÇOĞALGİL (Archives of Rheumatology, 2016)
We read the article published by Erkol İnal et al.(1) with great interest. The authors evaluated the associations between neutrophil-lymphocyte ratio (NLR), mean platelet volume, and platelet- lymphocyte ratio (PLR) along with disease activity in ankylosing spondylitis. They found that mean platelet volume is not associated with disease activity, whereas NLR and PLR may reflect disease activity. Although this is a well-written study, it has some methodological drawbacks. The researchers screened complete blood counts, erythrocyte sedimentation rate, C-reactive protein, disease activity, clinical status, and functional status of ankylosing spondylitis patients. They expressed inclusion and exclusion criteria. However, exclusion criteria of this study did not conform with those as noted in other studies.(2,3) They did not question the factors such as metabolic syndrome, anemia, secondary hyperparathyroidism, impaired thyroid function, chronic obstructive pulmonary disease, obstructive sleep apnea, connective tissue disease, allergic rhinitis, asthma and smoking history in the patient and control groups. These factors can affect NLR and PLR values. All these elements should be taken into account for determining exclusion criteria. Otherwise, incorrect findings may be obtained when the results are interpreted. The neutrophil, lymphocyte, and platelet counts can be simply obtained by a hemogram. NLR and PLR are important markers in determining subclinical inflammation, systemic inflammation, and prognosis of some diseases.(4) Thus, all confounding factors should be considered and detailed standardized methods must be used in determining NLR and PLR. Author Response Dear Editor, Our exclusion criteria were indicated in the manuscript as follows; • Inflammatory diseases other than ankylosing spondylitis (including connective tissue diseases, chronic inflammatory lung and respiratory diseases, etc.), • Infectious diseases, • Malignancies, • Cardiovascular diseases, • Diabetes mellitus, • Liver and kidney diseases. However, none of the patients had anemia or any other comorbid diseases such as hypothyroidism or hyperparathyroidism. Furthermore, none of the patients had not been smoking for two years before being included in the study. As pointed out, indicating all of these exclusion criteria in detail in the manuscript would have been more appropriate. Correspondence: Esra Erkol ‹nal, MD. Süleyman Demirel Üniversitesi Tıp Fakültesi Fiziksel Tıp ve Rehabilitasyon Anabilim Dalı, 32260 Isparta, Turkey. Tel: +90 507 - 563 65 11 e-mail: esraerkol@hotmail.com